Walls have feelings : architecture, film and the city - Shonfield, Katherine, 1954- (Routledge, 2003)
For the first time, this book brings the insights, methodologies and visions of film to the practice of architecture. Walls Have Feelings poses unanswered questions from our immediate past, crucial for the future of the city: what was the cultural mindset leading to the triumph of Brutalism? What is the urban and domestic impact of large scale office building? Are there alternatives to the planners' city of object? and, Why does your flat leak? This book uniquely brings to bear questions of urgent cultural relevance on critical design decisions. As such, it is of as much importance to architects, planners and students of design, as to students of cultural history, geography and all enthusiasts of cities and of film.